Comprehensive Review of Provocative and Instability Physical Examination Tests of the Shoulder. Issue 11 (1st June 2019) - Hippensteel, K. J.; Brophy, Robert; Smith, Matthew V.; Wright, Rick W.
Abstract : A detailed physical examination of the shoulder is crucial in creating a diagnosis in patients who present with shoulder pain. Tests of the cervical spine, scapula, and rotator cuff muscles have already been evaluated in a previous article. This article assesses provocative and instability examination tests of the shoulder. Descriptions on how the tests are performed and their diagnostic accuracy are presented.